1993
DOI: 10.1007/bf03215869
|View full text |Cite
|
Sign up to set email alerts
|

Salmeterol: An inhaled /β2-agonist with prolonged duration of action

Abstract: Salmeterol (Serevent) is an inhaled beta 2-receptor agonist with more than twelve hours' effect duration compared with 4-6 hours for the more short-acting substances bitolterol, fenoterol, salbutamol, and terbutaline. Salmeterol has been studied in several large-scale double-blind multicenter studies with up to one year's duration. More than 6,000 asthmatics have been treated with salmeterol during these controlled studies. All studies show salmeterol to have a significantly better and well-maintained bronchod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Although isoproterenol has been shown to inhibit the neutrophil respiratory burst [12,13], the widely used 2 -agonist salbutamol appears to be ineffective, at least using macrophages [14]. Moreover, the recently developed long-acting 2 -agonist salmeterol [15], possibly endowed with potential anti-inflammatory properties [16], was found to be incapable of inhibiting the respiratory burst in guinea pig eosinophils [17]. Therefore, we planned the present work to study the effects of salbutamol and salmeterol on the neutrophil respiratory burst and on the aforementioned PGE 2 -and PDE-IV-mediated regulation of this neutrophil response.…”
Section: Introductionmentioning
confidence: 99%
“…Although isoproterenol has been shown to inhibit the neutrophil respiratory burst [12,13], the widely used 2 -agonist salbutamol appears to be ineffective, at least using macrophages [14]. Moreover, the recently developed long-acting 2 -agonist salmeterol [15], possibly endowed with potential anti-inflammatory properties [16], was found to be incapable of inhibiting the respiratory burst in guinea pig eosinophils [17]. Therefore, we planned the present work to study the effects of salbutamol and salmeterol on the neutrophil respiratory burst and on the aforementioned PGE 2 -and PDE-IV-mediated regulation of this neutrophil response.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, long-acting β 2 -agonists for inhalation, such as formoterol and salmeterol, have been developed. Both these drugs have been shown to cause bronchodilation for at least 12 h after single dose administration [1][2][3][4]. Twice daily treatment with inhaled formoterol or salmeterol has been shown to reduce diurnal airway calibre fluctuations and asthma symptoms [5][6][7], and inhaled long-acting β 2 -agonists are therefore important components in the therapy of patients with chronic asthma, who are not fully controlled with inhaled anti-inflammatory therapy [8].…”
mentioning
confidence: 99%
“…Both compounds, when administered as an aerosol by a metered-dose inhaler (MDI) or when inhaled as a powder, have the property of retaining a bronchodilatory effect for up to 12 h, which accounts for their use in patients with nocturnal asthma. Moreover, the long duration of action allows for a twice daily treatment frequency, for example, on arising in the morning and on going to bed at night, which could be helpful in promoting patient compliance [1][2][3][4][5][6].In vitro work and noncomparative studies on formoterol and salmeterol have shown evidence that there are small differences between the two inhaled drugs with regard to the speed of onset of a bronchodilatory effect, duration of action and dose-dependency of the duration of effect [6][7][8][9][10][11][12][13]. At the present time, a few comparative studies in patients with chronic obstructive pulmonary disease (COPD) have been published [14,15], however, a direct comparison of the profile of the bronchodilatory effect in asthma is still lacking.…”
mentioning
confidence: 99%
“…In vitro work and noncomparative studies on formoterol and salmeterol have shown evidence that there are small differences between the two inhaled drugs with regard to the speed of onset of a bronchodilatory effect, duration of action and dose-dependency of the duration of effect [6][7][8][9][10][11][12][13]. At the present time, a few comparative studies in patients with chronic obstructive pulmonary disease (COPD) have been published [14,15], however, a direct comparison of the profile of the bronchodilatory effect in asthma is still lacking.…”
mentioning
confidence: 99%